Surface representations using blossoms and buds - Yohanes, S.L. (2008 IEEE International Conference on Shape Modeling and Applications, 2008)
Shape representations using polynomials in computer-aided geometric design (CAGD) and computer graphics are ubiquitous. This paper shows that any bivariate polynomial p(t,u) of total degree d les n can be represented in the form of a blossom of another bivariate polynomial b(t, u) of total degree d evaluated off the diagonal at the linear function pairs (Xj(t),Yj(u)), j = 1,... ,n, chosen under some conditions expressed in terms of symmetric functions. The bivariate polynomial b(t,u) is called a bud of the bivariate polynomial p(t,u). An algorithm for finding a bud b(t,u) of a given bivariate polynomial p(t,u) is presented. Successively, a bud of b(t, u) can be computed and so on, to form a sequence of representations. The information represented by the original bivariate polynomial is preserved in its buds. This scheme can be used for encoding/decoding geometric design information. The objects in the encoding/decoding sequence can be rendered graphically and manipulated geometrically like the usual parametric representations. Examples concerning triangular Bezier patches are provided as illustrations.